Inflammatory disease of the central nervous system induced by anti‐GD2 monoclonal antibody in a patient with high risk neuroblastoma. Issue 8 (17th February 2014) - Zama, Daniele; Morello, William; Masetti, Riccardo; Cordelli, Duccio Maria; Massaccesi, Erika; Prete, Arcangelo; Pession, Andrea
<x xml:space="preserve">Abstract</x> Pediatr Blood Cancer 2014; 61:1521–1522. © 2014 Wiley Periodicals, Inc.